2010
DOI: 10.1002/lt.21998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different immunoprophylaxis regimens after liver transplantation with hepatitis B core antibody-positive donors: A systematic review

Abstract: Orthotopic liver transplantation (OLT) recipients without hepatitis B virus (HBV) infection who receive liver grafts from antibody to hepatitis B core antigen-positive [HBcAb(þ)], hepatitis B surface antigen-negative [HBsAg(À)] donors have an increased risk of developing de novo hepatitis B infection. We compared the 2 most commonly employed prophylactic regimens-lamivudine (LAM) monotherapy and hepatitis B immunoglobulin (HBIG)þLAM combination therapy-to determine the relative efficacies of these 2 protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 31 publications
3
89
0
6
Order By: Relevance
“…It is also very important to utilize prophylaxis regimens to prevent the reactivation of HBV infection in patients who receive organ transplants, especially due to HBV-related liver diseases [67]. Nowadays, pediatric liver transplantation is mainly indicated for biliary atresia, metabolic diseases, genetic diseases, and so on [68].…”
Section: Immunocompromised Hosts and Occult Infectionmentioning
confidence: 99%
“…It is also very important to utilize prophylaxis regimens to prevent the reactivation of HBV infection in patients who receive organ transplants, especially due to HBV-related liver diseases [67]. Nowadays, pediatric liver transplantation is mainly indicated for biliary atresia, metabolic diseases, genetic diseases, and so on [68].…”
Section: Immunocompromised Hosts and Occult Infectionmentioning
confidence: 99%
“…Das Risiko nimmt zu, wenn der Spender HBsAg-("hepatitis B surface antigen") oder sogar HBeAg-positiv (HBeAg: "hepatitis B envelope antigen") ist. Entschließt man sich trotzdem zur Transplantation, sollte der Empfänger mit Lamivudin prophylaktisch behandelt werden [14].…”
Section: Immunglobuline Und Hyperimmunglobulineunclassified
“…9 2 years Chang [37] HBIG 100 IU/Kg IV intraoperatively and then daily 9 3 days, followed by booster to maintain anti-HBs [20 IU/L plus vaccination based on anti-HBs titer Fabrega [38] HBIG 10,000 IU IV during anhepatic phase and then daily 9 7 days plus LAM 100 mg daily ¥ Nery [29] HBIG 10,000 IU IV intraoperatively and then daily 9 7 days, weekly 9 1 month, and monthly 9 6 months and/or LAM 150 mg daily lifelong } Lee [15] HBIG (100 IU/Kg for children and 10,000 IU for adults) IV daily 9 7 days, followed by booster to maintain antiHBs [ 200 IU/L Suehiro [39] HBIG 10,000 IU IV during anhepatic phase and then 2,000 IU IV daily 9 7 days, followed by 2,000 IU IV every 2 months to maintain anti-HBs [ 100 IU/L plus LAM 100 mg daily Donataccio [24] HBIG 10,000 IU IV during anhepatic phase and then daily that current available studies do not support prophylactic use of the combination therapy over LAM monotherapy in HBV DNA negative patients receiving anti-HBcpositive liver grafts. LAM monotherapy has the same efficacy as the combination therapy at far less cost [47,48]. However, drug-resistance HBV mutants have been reported as the cause of DNH in a case after being on LAM for more than 3 years [42].…”
Section: Prophylaxis Strategies For Dnhmentioning
confidence: 99%
“…These findings argue that HBIG may be a dispensable part of prophylaxis. In a recent systemic review, Saab et al [47] reported the incidence of DNH was 2.7% in patients receiving LAM-only prophylaxis versus 3.6% in those receiving HBIG plus LAM combination therapy. In another systemic review, Cholongitas reported that DNH rates were 19, 2.6, and 2.8% in HBsAg-negative recipients under HBIG, LAM, and their combination, respectively.…”
Section: Prophylaxis Strategies For Dnhmentioning
confidence: 99%
See 1 more Smart Citation